Success formula of the Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of the Kharkiv Regional Council: 105 years of experience of pedagogical skills - Ponomarova, Halina; Kharkivska, Alla; Petrychenko, Larisa (My University, 2025)
The monograph highlights the 105-year path of formation and development of the Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of the Kharkiv Regional Council. The key areas of the historical development of the institution, the dynamics of ups and downs, difficulties and challenges faced by the institution's employees and students are presented. Articles by teachers and the administration of the academy are included, which highlight the stages of formation and development of individual structural units and the institution as a whole, as well as the achievements of students, pedagogical and scientific and pedagogical workers who jointly form the educational space of the academy. The materials in the scientific work allow us to understand the value of the academy and each of its team members as a driving force in the effective professional training of competitive specialists. The monograph is intended for graduates and students of higher education, teachers of pedagogical institutions of higher education and all interested persons who want to learn more about the activities of the academy's representatives.
Success formula of the Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of the Kharkiv Regional Council: 105 years of experience of pedagogical skills: international collective monograph / edited by H. Ponomarova, A. Kharkivska, L. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of the Kharkiv Regional Council. Publishing house OKTAN PRINT s.r.o., 2025. 894 p.
Keywords: key areas of the historical development of the institution, stages of formation and development of individual structural divisions of the institution as a whole, the formation of the educational space of the academyб